PENGEMBANGAN BUDIDAYA SORGUM TANAMAN PANGAN ALTERNATIF PADA DAERAH BAYANGAN HUJAN DI NAGARI RAMBATAN KABUPATEN LIMA PULUH KOTA - Eka Candra Lina; Wenny Surya Murtius (LPPM Universitas Andalas, 2020)
Sorghum is an adaptive plant, can grow optimally on dry and acid soil and is resistant to marginal conditions (drought, salinity, and acid soils). This plant has benefits from carbohydrates to replace rice and can be processed into other derivative products. People consume sorghum that is processed traditionally, among others, made porridge or steamed and enjoyed immediately. Also, with proper processing, it can make sorghum potential health functional food. This activity aims to improve the economy of the surrounding community by providing knowledge and information related to sorghum processing and cultivation. Activities were carried out in the form of counseling, training, and mentoring. At the end of the program, a technology transfer can increase people's knowledge and income in Nagari Rambat. The activity results found that Jorong Pabalutan and Dusun Ladang Laweh were located in Nagari Rambat, Rambat District, Tanah Datar Regency, West Sumatra. Nagari Rambat has 1,550 families, the majority of whom are rice farmers in the fields, tapping rubber. The area of ​​rice fields in Nagari Rambat is around 27,442 hectares. The general condition faced by farmers is irrigation problems; farmers only plant rice in the fields twice a year, even only once a year. This is because the propagation is a rain shadow area. One of the efforts to fill the void of land during the dry season is by cultivating sorghum. Furthermore, the Sepakat farmer groups' survey results and the Kuta Bali farmer groups show a strong desire to obtain a transfer of knowledge and technology related to proper and correct sorghum cultivation.